HUBUNGAN SIKLUS MENSTRUASI DENGAN KADAR KALSIUM GINGIVAL CREVICULAR FLUID PENDERITA PERIODONTITIS KRONIS - Amilia Ramadhani; Ziyada Salisa; Fani Tuti Handayani (Scripta Biologica, 2018)
Background: Periodontal disease is commonly caused by Porphyromonas gingivalis that released lipopolysaccharide endotoxin (LPS). The stimulation of pro-inflammatory cytokines secretion in periodontal tissue is not only derived from pathogenic bacteria. Various genetic conditions and systemic conditions are also being the trigger factor. One of systemic factor is sex hormones such as estrogen and progesterone. Both of these hormones fluctuate during the menstrual cycle. Purpose: The purpose was to determine the relationship of menstrual cycle based on ovarian cycle with calcium gingival crevicular fluid (GCF) levels in chronic periodontitis patient. Methode: This research was analytic observation. The samples in this reasearch were 9 women who aged 17-45 years with a diagnosis of chronic periodontitis and had a normal menstrual cycle (21-35 days). All subjects were calculated menstrual cycle and determined the phase of follicular, ovulation, and luteal. Clinical examination and GCF sampling were performed at each phase. Measurement of calcium GCF level was done using spectrophotometer. Result: During follicular phase of menstruation cycle, the periodontal index arises until 1,62, meanwhile the highest calcium concentration occurred in ovulation phase of menstruation cycle. Linier regression correlation test showed no significant correlation between periodontal index, calcium concentration and menstruation cycle. Conclusion: Fluctuation in women’s sexuality hormones during menstruation cycle do not related to alveolar bone damage and GCF’s calcium concentration.